Probe-based confocal laser endomicroscopy (pCLE): a preclinical investigation of the male genital tract. Issue 1 (January 2016) - Trottmann, Matthias; Sroka, Ronald; Stepp, Herbert; Liedl, Bernhard; Becker, Armin; Stief, Christian; Kölle, Sabine
Abstract The aim of this study was to assess the potential of probe-based confocal laser endomicroscopy (pCLE) as a new diagnostic imaging technique for the male genital tract. For this purpose, testes, epididymides, and vasa deferentia were obtained during transsexual surgery of healthy patients (n  = 10, 26–52 years). Prior to this, testes of rats (n  = 10, Sprague–Dawley) and mice (n  = 8, wild-type) were examined. Ex vivo tissues were investigated by pCLE after topical fluorescence staining. Images and pCLE real-time video sequences were compared to images acquired by confocal laser scanning microscopy (CLSM); this allowed the identifying of corresponding microstructures. Interestingly, the seminiferous tubules of transsexual humans contained mainly spermatogonia due to long-term estrogen treatment, whereas the seminiferous tubules of the murine and rat spermatogenesis-related cell types were differentiated. Mosaicking improved the inspection potential by wide-angle views. Similarly, the microarchitecture of the epididymis and the vas deferens was successfully visualized in situ and on a cellular level by pCLE. In summary, pCLE allows for real-time identification of relevant microstructures responsible for spermatogenesis under ex vivo conditions. Additionally, pCLE enabled to localize vital spermatozoa in the testis thus opening up new ways to improve sperm retrieval rates during assisted reproduction. Both clinically relevant experiences hold promise to introduce this diagnostic method into a clinical study, and to investigate its potential as a clinical diagnostic procedure to expedite and improve the medical situation.